2015
DOI: 10.1021/acsphotonics.5b00112
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Janus Role of Mie Resonances and Leaky/Guided Modes in Semiconductor Nanowire Absorption for Enhanced Light Harvesting

Abstract: Light absorption from finite semiconductor nanowires is investigated through a unified theoretical picture and numerical simulations. We first show theoretically from the electromagnetic mode dispersion relation and the Mie extinction cross sections for infinite nanowires that formally equivalent (Janus) formulas yield both leaky/guided modes and Mie resonances as, respectively, complex wave vector or complex frequency solutions that, in turn, overlap only at grazing angles with respect to the nanowire axis. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 43 publications
10
110
0
Order By: Relevance
“…A similar deviation toward glancing angles was found by Abujetas et al for the absorption cross section of optically thin InP nanowires [45]. Instead of the angular dispersion seen in the infinite cylinder, the mode spectrum for a finite wire consists of a well defined set of localized modes with fixed resonance frequencies.…”
Section: Varying the Angle Of Incidencesupporting
confidence: 81%
See 3 more Smart Citations
“…A similar deviation toward glancing angles was found by Abujetas et al for the absorption cross section of optically thin InP nanowires [45]. Instead of the angular dispersion seen in the infinite cylinder, the mode spectrum for a finite wire consists of a well defined set of localized modes with fixed resonance frequencies.…”
Section: Varying the Angle Of Incidencesupporting
confidence: 81%
“…7(g,h)). Comparison of both the mode symmetry and spectral position with the infinite cylinder case [45] shows that the a 3 2 mode coincides with the first hybrid leaky mode, HE 11 , which may explain the enhanced excitation of this particular mode toward glancing angles.…”
Section: Varying the Angle Of Incidencementioning
confidence: 89%
See 2 more Smart Citations
“…[ 9,10 ] Recent theoretical and experimental works have revealed that light coupling into leaky guided modes is responsible for the resonant optical absorption at grazing light incidences with respect to the nanowire axis, while Mie resonances play a critical role mostly at nongrazing incidences. [11][12][13] The leaky/guided mode resonances in simple cylindrical nanowires occur at specifi c resonance wavelengths that depend on the nanowire diameter, and the free spectral range between these resonances can be extremely large in such cylindrical nanowire resonators, resulting in the enhancement of optical absorption only in specifi c spectral regions near the resonance wavelengths. [ 14,15 ] Dual-or multiple-diameter nanowire arrays may exhibit resonances with an increased spectral density, thereby enhancing the optical absorption over a broad spectral range.…”
Section: Doi: 101002/adma201505144mentioning
confidence: 99%